Measuring perceived service quality using SERVQUAL: a case study of program technorama IT provided by IT advancement section (KIT) at rural area of Sabah (Nabawan) / Mohammad Zulikiflee Yusof - Yusof, Mohammad Zulikiflee (2016)
This research is conducted to identify what are the factors and the most importance factor influencing the participant perceived service quality towards program of technorama-iT that provided by IT Advancement Section (KIT) at rural area of Sabah (Nabawan) by using SERVQUAL dimension model such as Responsiveness, Tangibles, Reliability, Assurance and Empathy.